Superficial acral fibromyxoma of the thumb: a case report - Souza, Bruno Gonçalves Schroder e (2013)
The authors report a case of superficial acral fibromyxioma (SAF) in a 74-year-old male who presented with a painless mass in a periungual dorsoradial region of the right thumb. It is a rare benign neoplasm, which was recently described, that arouse on the skin and subcutaneous tissue of the hands and feet, especially in the proximity to the ungual region of male adults. Surgical treatment was performed with the excision in blocks of the margins of the lesion and fragmentation of the nail and nail matrix, according to the literature recommendation. Although there may be local recurrence in 22% of the cases, the patient presents no symptoms, deformities or functional limitations. In addition, there was no sign of tumor recurrence 18 months after the surgery. We are not aware of a similar case report in the Brazilian literature